Parasitological and molecular diagnosis of Trypanosoma theileri in cattle sampled in the extreme south of São Paulo, SP, Brazil - Amaral, Dayvid; Emiliano de Silva, Ryan; Ap. Nieri-Bastos, Fernanda; Marcili, Arlei (Brazilian Journal of Global Health, 2021)
OBJETIVO: O Trypanosoma theileri é a espécie-tipo do subgênero Megatrypanum, foi registrado pela primeira vez em bovinos na África do Sul e na África Oriental. As criações de bovinos no extremo sul do munícipio de São Paulo e de Embú-Guaçu, são caracterizadas como de subsistência em propriedades pequenas, foram registradas 500 cabeças de gado no ano de 2019. Esse trabalho objetivou avaliar a ocorrência de T. theileri em bovinos de criações familiares no extremo sul do município de São Paulo e do munícipio de Embu-Guaçu, SP, Brasil. MÉTODOS: Realizou-se diagnóstico parasitológico e molecular em amostras colhidas de 68 bovinos em propriedades de pequeno porte no extremo sul de São Paulo. RESULTADOS: O diagnóstico molecular específico para T. theileri apresentou positividade de 17,6% (12/68) e o diagnóstico parasitológico de 5,8% (4/68). CONCLUSÃO: Apesar de considerado não patogênico, sua presença no hospedeiro pode favorecer outras doenças parasitárias e infecciosas. DESCRITORES: Tripanossomíases, Tabanídeos, Ruminantes, PCR. ABSTRACT OBJECTIVE: Trypanosoma theileri is the type species of the subgenus Megatrypanum, first registered in cattle in South Africa and East Africa. Cattle farms in the extreme south of the municipality of São Paulo and Embu-Guaçu, are characterized as subsistence, on small properties, and 500 head of cattle were registered in 2019. This work aimed to evaluate the occurrence of T. theileri in cattle from family farms in the extreme south of the city of São Paulo and in the municipality of Embu-Guaçu, SP, Brazil. METHODS: Parasitological and molecular diagnoses were carried out on samples taken from 68 cattle in small farms in the extreme south of São Paulo. RESULTS: The specific molecular diagnosis of T. theileri was 17.6% positive (12/68) and the parasitological diagnosis was 5.8% (4/68). CONCLUSION: Although considered non-pathogenic, its presence in the host may favor other parasitic and infectious diseases. DESCRIPTORS: Trypanosomiasis, Tabanids, Ruminants, PCR.